ASSESSING NIGERIA'S CAPACITY TO HOST MEGA EVENTS: A STUDY OF AFRICA CUP OF NATIONS (AFCON), 2023 - AREMU Samuel Olabisi; OSUOHA Ifeanyi Jude (American Journals, 2025)
Sporting events have assumed a major social-recreational and economic activities nationally and globally, making them to require sufficient capacity for the hosting.
Keywords: Capacity, Facility, Mega, Sports, Tourism.